Besnoitiosis in Donkeys in the United States - Sally DeNotta (EDIS, 2023)
Besnoitiosis is a skin condition affecting donkeys in Florida and throughout the United States. This publication discusses the condition as well as clinical findings, diagnosis, prevention, and therapy. Written by Sally DeNotta, and published by the UF/IFAS Veterinary Medicine—Large Animal Clinical Sciences Department, January 2023.